The fundamentals of brain development: integrating nature and nurture - Stiles, Joan (Henry Stewart Talks, 2010)
Brain Development, Psychological models of inheritance and development, and the nature nurture debate, Biological models of inheritance, Brain development as a dynamic process, Five examples (1) differentiation of neural progenitors (2) embryonic differentiation of neocortex (3) visual experience and the early development of primary visual cortex (4) rewiring cortex (5) altering organization in the adult brain, Brain development as the dynamic interaction of nature and nurture